Lack of evidence for close linkage of the glutamate GluR6 receptor gene with schizophrenia. - Chen, AC; Kalsi, G; Brynjolfsson, J; Sigmundsson, T; Curtis, D; Butler, R; Read, T; Murphy, P; Petursson, H; Barnard, EA; Gurling, HM (1996)
OBJECTIVE: Previous research has consistently implicated genetic factors in the pathogenesis of schizophrenia. It has been hypothesized that an abnormality in glutamatergic function is of etiologic importance in schizophrenia, and therefore the glutamate receptor family of genes are potential susceptibility loci for schizophrenia. To test this hypothesis the authors sought to detect linkage between the GluR6 glutamate receptor gene and schizophrenia. METHOD: Twenty-three English and Icelandic families containing multiple cases of schizophrenia were genotyped with a microsatellite trinucleotide repeat polymorphism localized at the GluR6 glutamate receptor locus. Lod scores, model-free linkage analysis, and extended relative pair analysis were used to test for linkage. RESULTS: No statistically significant evidence of linkage between GluR6 and schizophrenia was found. CONCLUSIONS: The results do not support the hypothesis that GluR6 allelic variants provide a major gene contribution to the etiology of schizophrenia in a large proportion of these pedigrees.